Synaptic Organizers in Alzheimer’s Disease: A Classification Based on Amyloid-β Sensitivity - Lee, Alfred Kihoon; Khaled, Husam; Chofflet, Nicolas; Takahashi, Hideto (Frontiers in Cellular Neuroscience, 2020)
Synaptic pathology is one of the major hallmarks observed from the early stage of Alzheimer’s disease (AD), leading to cognitive and memory impairment characteristic of AD patients. Synaptic connectivity and specificity are regulated by multiple trans-bindings between pre- and post-synaptic organizers, the complex of which exerts synaptogenic activity. Neurexins (NRXs) and Leukocyte common antigen-related receptor protein tyrosine phosphatases (LAR-RPTPs) are the major presynaptic organizers promoting synaptogenesis through their distinct binding to a wide array of postsynaptic organizers. Recent studies have shown that amyloid-β oligomers (AβOs), a major detrimental molecule in AD, interact with NRXs and neuroligin-1, a NRX-binding postsynaptic organizer, to cause synaptic impairment. On the other hand, LAR-RPTPs and their postsynaptic binding partners have no interaction with AβOs, and their synaptogenic activity is maintained even in the presence of AβOs. Here, we review the current evidence regarding the involvement of synaptic organizers in AD, with focus on Aβ synaptic pathology, to propose a new classification where NRX-based and LAR-RPTP-based synaptic organizing complexes are classified into Aβ-sensitive and Aβ-insensitive synaptic organizers, respectively. We further discuss how their different Aβ sensitivity is involved in Aβ vulnerability and tolerance of synapses for exploring potential therapeutic approaches for AD.